Improved Quality of Death and Dying in Care Homes: A Palliative Care Stepped Wedge Randomized Control Trial in Australia. Issue 2 (4th November 2019) - Liu, Wai‐Man; Koerner, Jane; Lam, Lawrence; Johnston, Nikki; Samara, Juliane; Chapman, Michael; Forbat, Liz
Abstract : OBJECTIVES: Mortality in care homes is high, but care of dying residents is often suboptimal, and many services do not have easy access to specialist palliative care. This study examined the impact of providing specialist palliative care on residents' quality of death and dying. DESIGN: Using a stepped wedge randomized control trial, care homes were randomly assigned to crossover from control to intervention using a random number generator. Analysis used a generalized linear and latent mixed model. The trial was registered with ANZCTR: ACTRN12617000080325. SETTING: Twelve Australian care homes in Canberra, Australia. PARTICIPANTS: A total of 1700 non‐respite residents were reviewed from the 12 participating care homes. Of these residents, 537 died and 471 had complete data for analysis. The trial ran between February 2017 and June 2018. INTERVENTION: Palliative Care Needs Rounds (hereafter Needs Rounds) are monthly hour‐long staff‐only triage meetings to discuss residents at risk of dying without a plan in place. They are chaired by a specialist palliative care clinician and attended by care home staff. A checklist is followed to guide discussions and outcomes, focused on anticipatory planning. MEASUREMENTS: This article reports secondary outcomes of staff perceptions of residents' quality of death and dying, care home staff confidence, and completion of advance care planning documentation. We assessed (1) quality of death and dying, and (2) staff capability of adopting a palliative approach, completion of advance care plans, and medical power of attorney. RESULTS: Needs Rounds are associated with staff perceptions that residents had a better quality of death and dying ( P < .01; 95% confidence interval [CI] = 1.83‐12.21), particularly in the 10 facilities that complied with the intervention protocol ( P < .01; 95% CI = 6.37‐13.32). Staff self‐reported perceptions of capability increased ( P < .01; 95% CI = 2.73‐6.72). CONCLUSION: The data offer evidence for monthly triage meetings to transform the lives, deaths, and care of older people residing in care homes. J Am Geriatr Soc 68:305–312, 2020